EFFECT OF PHYTOECDYSTEROID ON SILK PRODUCING POTENTIAL OF MULTIVOLTINE MULBERRY SILKWORM BOMBYX MORI LINN - K. SRIVASTAVA,; V. B. UPADHYAY, (The Bioscan, 2012)
Effect of phytoecdysteroid on silk producing potential of multivoltine mulberry silkworm Bombyx mori was studied. Experiments were performed by 40, 50, 60 and 70% concentration of phytoecdysteroid obtained from Achyranthes leaf extract. A control set was always maintained with each set of experiment. Maximum shell ratio (15.45 ± 1.07) was noticed to be in case of the double treatment (IV and V instar larvae were treated) by 60% phytoecdysteroid and minimum (12.25 ± 0.831) was recorded in triple treatment (III, IV and V instar larvae were treated) by 70% phytoecdysteroid concentration. Phytoecdysteroid treatment,if applied tactfully,may be useful for boosting up the sericulture industry as well as the economy of silkworm rearing.